Extensive and invasive lymphangioma circumscriptum in a young female: A rare case report and review of the literature - Mohan H Kudur; Manjunath Hulmani (Wolters Kluwer Medknow Publications, 2013)
Lymphatic malformations, or lymphangiomas, are benign proliferations of lymphatics, classified as superficial lymphangioma circumscriptum (LC) and deep (cavernous lymphangioma). LC, as the name suggests, is a well-circumscribed lesion but, rarely, extensive and invasive forms can also be seen. Surgical excision is the main modality of treatment. We report a case of extensive and invasive type of LC where surgical excision is difficult and recurrence is the rule.